Monitoring differentiated thyroid cancer patients with negative serum thyroglobulin - Nam, H.-Y.; Paeng, J.C.; Chung, J.-K.; Kang, K.W.; Cheon, G.J.; Kim, Y.; Park, D.J.; Park, Y.J.; Min, H.S.; Lee, D.S. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: Serum antithyroglobulin antibody (TgAb) has been reported as a surrogate marker for differentiated thyroid cancer (DTC) in some conditions. We investigated changes in serum TgAb levels after stimulation with thyroid- stimulating hormone (TSH) and the clinical implications for monitoring DTC. Patients, methods: We retrospectively enrolled 53 DTC patients who had undergone total thyroidectomy and were negative for serum Tg and positive for TgAb. Patients underwent highdose radioactive iodine treatment, and serum TgAb was measured before (TgAbBAS) and after TSH stimulation (TgAbSTIM). TgAb was followed up 6 to 12 months later (TgAbF/U). The change in TgAb after TSH stimulation ΔTgAb- STIM) was calculated as a percentage of the baseline level. Patient disease status was classified into no residual disease (ND) and residual or recurred disease (RD) by follow-up imaging studies and pathologic data. The characteristics and diagnostic value of serum TgAb levels and ΔTgAbST|M were investigated with respect to disease status. Results: 38 patients were in the ND group and 15 were in the RD group. TgAbBAS, TgAbSTIM and TgAbF/U were significantly higher in the RD compared to the ND group (p = 0.0008, 0.0002, and < 0.0001, respectively). ΔTgAbSTIM was also significantly higher in the RD group (p = 0.0009). In the patients who presented with obviously high (> 50%) or low (< -50%) ΔTgAbSTIM, the proportions in the RD group were markedly different at 100% and 7%, respectively. ΔTgAbSTIM had significant diagnostic value for RD (p < 0.001). Conclusion: The change in serum TgAb level after TSH stimulation is different between the RD and ND groups, and thus, it may be used as a surrogate diagnostic marker for DTC when the serum Tg is negative and TgAb is positive.
Keywords: Differentiated thyroid cancer; thyroglobulin; antithyroglobulin antibody; thyroid-stimulating hormone